Monetary Policy Transmission to the Labour Market – Evidence From the Polish Economy - Włodarczyk, Przemysław (Olsztyn Economic Journal, 2017)
This article verifies the hypothesis of a short-run impact of undertaken monetary policy on the labour market stance, advocated by the Keynesian/monetarist strand of economic theory. The analyses are performed within a small open economy framework, using data with regards to Poland in the 2000:1–2016:5 period. The research takes into account the high volatility of economic processes in the developing economies as well as their natural business cycle fluctuations and uses Markov Switching Bayesian Structural Vector Autoregressive models. The presented results confirm that there exists a nexus between monetary policy and the levels of output, inflation and the real effective exchange rate in the Polish economy. There is however no statistically significant relation between the employment level and changes in monetary policy. In this respect, the results are in line with the monetarist theory rather than with the traditional Keynesian ew Keynesian view.